PENINGKATAK KOMPETENSI MAHASISWA PENINGKATAN KOMPETENSI MAHASISWA DEPARTEMEN ADMINISTRASI PENDIDIKAN MELALUI PROGRAM MAGANG DI MTS AL-ARAFAH - bahrudin, Canra (Servirisma, 2024)
The internship program is a crucial component of higher education curricula, designed to equip students with practical competencies, particularly in the field of Educational Administration. This study aims to analyze the effectiveness of the internship program in enhancing the competencies of students in the Educational Administration Program at Universitas Muhammadiyah Bogor Raya through direct practice at MTs Al-Arafah. The internship program involved second, fourth, and sixth-semester students. The implementation methods included preparation, execution, mentoring, and evaluation stages. The internship results revealed an improvement in students' technical competencies, particularly in managing student data using digital tools such as Google Forms integrated with Microsoft Excel. Additionally, students experienced enhanced analytical skills, report writing abilities, and interpersonal skills through guidance from faculty mentors. This internship program not only provided students with hands-on work experience but also prepared them to face future challenges in the field of educational administration. The conclusion highlights the program's effectiveness in shaping student competencies, although continuous development of the digital products created is necessary to better meet the needs of schools.